Postinfarction remodeling of the left ventricle of heart and the phase of reparative fibrosis - L. B. Kim; V. Yu. Kulikov; N. G. Minina (Атеросклероз, 2010)
Postinfarction remodeling of heart is based on the biochemical processes that take place in connective tissue structures that surround the nidus of necrosis and those that located at some distance from it. They are to provide recovery of the organ function through the structural changes of myocardium, formation of the full healing tissue with newly synthesized collagen, fibronectin and glucosaminoglucans (proteoglycans). Biochemcial processes providing postinfarcion fibrosis and remodeling of the heart may be modified udnert he action of medical preparations. Cell therapy involing transplantation of cambial cells into the injured organ is considered as a promising method in rehabilitation of acute myocardial infarction, but this method may not be recommended for a broad range of patients because it is too expensive and complicated. In this connection, development of approaches to govern heart remodeling, to prevent the transition of the adaptive version of remodeling into the pathological one with the help of medical preparations appears as a long-term but more available method of rehabilitation for the major group of patients.